Analysis of Travel Notes of Francesco Balducci Pegolotti - Mukhametkali, Alisher Anuarovich; Teleuova, Elmira Teshebaevna (Journal of Ecohumanism, 2024)
The study of medieval trade routes and economic ties between the West and the East is of particular relevance for understanding the formation of the modern global economy and globalization processes. Travel notes of Francesco Balducci Pegolotti, set out in his work "The Practice of Commerce" ("La Pratica della Mercatura"), are a unique and little-studied source of information on trade routes, goods and commercial practices of the 14th century. However, despite the significance of this document, its limited study within Russian historiography justifies selecting it as the research focus. The purpose of the article is to identify and analyze the main trade routes and economic ties described in Pegolotti’s travel notes for understanding international trade and cultural exchange in the 14th century. The leading approach is theoretical analysis using historical-philological, comparative, and geographical methods to reconstruct trade routes and assess their impact on economic and cultural relations between the West and the East. Author’s results. The hypothesis about the importance of Pegolotti’s work for reconstructing trade routes and the economic structure of the Middle Ages is confirmed. The study reveals that detailed descriptions of trade routes, goods, and measures of weight in his work allow us to understand international trade of that time and reveal the complexity of commercial transactions between different regions. It is substantiated that Pegolotti’s travel notes serve as a valuable source for studying the economic, social, and cultural aspects of medieval trade. The practical and theoretical significance of the results lies in filling gaps in the study of medieval trade and opening new perspectives for research that integrates history, economics, linguistics, and cultural studies.